THE ROLE OF FIRM SIZE IN MODERATING GREEN ACCOUNTING, INNOVATION, AND STAKEHOLDER ENGAGEMENT ON FIRM VALUE - Amalia Indah Fitriana (Universitas Muhammadiyah Tangerang, 2026)
Objective: This study examines the moderating role of firm Size in the relationships among green accounting, green product innovation, stakeholder involvement, and firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024.Method: A quantitative approach was employed using panel data regression analysis (Eviews 12) on a sample of manufacturing firms.Results: The findings reveal that: (1) green accounting negatively affects firm value; (2) green product innovation also negatively affects firm value; (3) stakeholder involvement has no significant effect; (4) firm Size significantly moderates the effect of green accounting on firm value, but (5) firm Size does not moderate the effects of green product innovation or stakeholder involvement.Novelty: This study offers three key novelties. First, it provides empirical evidence from an emerging market (Indonesia), where sustainability practices are still voluntary, in contrast to prior studies from developed countries with mandatory disclosure regimes. Second, it demonstrates that firm size acts as a pure moderator selectively only for green accounting, not for innovation or stakeholder engagement, refining contingency theory in the context of environmental strategy. Third, unlike most prior research that assumes linear positive effects, this study reveals short-term value destruction from green practices, challenging the conventional